A review of campfire burns in children: The QLD experience. Issue 5 (August 2018) - Okon, O.; Zhu, L.; Kimble, R.M.; Stockton, K.A.
Highlights: Campfire burns cause significant morbidity. Burns are often sustained from incorrectly extinguished campfires. Burns first aid is often not performed properly by the public. Targeted campaigns can help reduce the incidence of campfire injuries. Abstract: Introduction: Campfire burns in children are a significant health issue. It is imperative that the extent of the problem is examined and strategies discussed to inform future prevention campaigns. Method: A retrospective review of data from the Queensland Paediatric Burns Registry for all children presenting with campfire burns between January 2013 and December 2014 (inclusive). Information collected included patient demographics, detail regarding mechanism of injury, first aid, Total Body Surface Area (TBSA), burn depth, and treatment. Results: Seventy-five children with campfire burns were seen in our paediatric burns centre during this 2-year period. The median age of patients was 3 years (range 10 days–14 years). The hands and feet were the areas most commonly affected. Eleven percent of patients suffered flame burns, whilst 89% suffered contact burns from the hot coals or ashes. Of the latter group, approximately half experienced burns from campfires that had been extinguished for at least one night. Thirteen percent of patients underwent split thickness skin grafting. The incidence of burns was increased during school holiday months. Discussion: We have previously demonstrated the effectiveness of targeted campaigns in reducing the incidence of campfire burns. A significant portion of patients sustained burns from incorrectly extinguished campfires. These injuries are likely to be preventable with ongoing public awareness campaigns.